Molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material as well as preparation method and application thereof
By introducing molybdenum and tungsten into niobium oxide and preparing molybdenum niobium tungsten oxygen fast-charge negative electrode material by high-temperature calcination, the problem of capacity attenuation of existing niobium oxide materials during high magnification and long cycles is solved, and the improvement of high capacity, long life and fast charging performance is achieved.
Patent Information
- Application Number
- CN202411900020.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
AI Technical Summary
The existing niobium oxide anode materials have capacity attenuation problems during high magnification and long cycles, mainly due to the lattice distortion caused by the gap cation electrostatic repulsion and the Ginger Taylor effect during electrochemical processes.
By dissolving the molybdenum, niobium and tungsten sources in an acidic solution, forming a gel, and dehydrating the gel, the molybdenum niobium tungsten oxygen fast-charge negative electrode material is prepared by high-temperature calcination. The method includes high-temperature vacuum drying, low-temperature pre-firing, pressing into a round cake shape and re-temperature calcining to obtain a material with high capacity and rate properties.
The capacity retention rate of the material for 2,000 cycles at a high 50C ratio reaches 87%, while avoiding the problem of low compaction density of nanoparticles, significantly improving electrochemical performance and cycle life.
Smart Images

Figure CN119660798A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material and a preparation method and application thereof. Background Art
[0002] High capacity, safe operation, fast charge and discharge, and long life are the basic properties of lithium-ion batteries in large-scale energy storage applications such as electric vehicles. It is well known that the anode material mainly limits the improvement of power density. Among the existing anode materials, conversion-type and alloy-type anodes with high theoretical capacity show great volume expansion, resulting in severe capacity decay and low Coulombic efficiency. Niobium-based oxides are candidates for embedded anode materials for lithium-ion batteries due to their high rate capability, high capacity, and safe operating voltage, but their inherent low conductivity and limited cycle life (generally less than 1000 cycles at high rate) hinder their practical application. Although the above problems can be alleviated by compounding with carbonaceous materials, the overall volume energy density will be reduced as a result.
[0003] Studies have shown that the introduction of tungsten atoms or titanium atoms into niobium oxides can improve the conductivity of such materials and show excellent electrochemical properties. The researchers prepared a series of niobium tungsten oxides and niobium titanium tungsten oxides through solution combustion, electrospinning, solid phase sintering, sol-gel and other methods. These materials all show good fast charging performance due to the Wadsley-Roth type crystal shear structure, but there is a significant capacity decay during higher rates (20C) and longer cycles (>1000 cycles). This may be due to the electrostatic repulsion between interstitial cations in the electrochemical process and the lattice distortion caused by the Jan-Taylor effect. This phenomenon is more serious at the tetrahedral junctions at the edges of the crystal structure, reducing the insertion rate of lithium ions.
[0004] Therefore, in order to further improve the rate performance of niobium oxide, it is necessary to suppress the octahedral distortion and reduce the maximum Li + Migration barriers are a viable option. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the present invention provides a molybdenum-niobium-tungsten-oxygen fast-charge negative electrode material and a preparation method thereof. The method is simple and efficient, and the prepared material has high capacity and rate performance.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] In the first aspect, the present invention provides a method for preparing a molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material, wherein a molybdenum source, a niobium source and a tungsten source are dissolved in an acidic solution, and a certain amount of an organic solution is prepared at the same time. The two solutions are fused together to form a gel, and an organic-inorganic mixed solid is obtained after dehydration treatment. The molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material is prepared by a high-temperature calcination method.
[0008] Furthermore, the specific steps of the high-temperature calcination method are: drying the gel under high-temperature vacuum conditions to obtain an organic-inorganic mixed solid, pre-burning it at a low temperature to obtain a precursor, pressing the precursor into a round cake shape and then calcining it at a high temperature to obtain a molybdenum niobium tungsten oxygen fast-charging negative electrode material.
[0009] Furthermore, during the high temperature vacuum process, the temperature is within the range of 80 to 160° C., the vacuum degree is within the range of 0.8 to 1.0 MPa, and the time is within 10 to 15 hours; the mixed solid is kept at 300 to 450° C. for 6 to 8 hours to obtain a precursor.
[0010] Among them, a vacuum environment is easier to remove the material itself and even the crystal water.
[0011] Furthermore, the precursor is pressed into a cake shape at a pressure of 500 to 1000 MPa; and the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material is obtained by keeping the temperature at 700 to 1000° C. for 5 to 10 hours.
[0012] Among them, pressing into a cake shape makes it easier for substances to diffuse and improves crystallinity.
[0013] Furthermore, the acidic solution is prepared by deionized water and an organic acid, and the pH value of the acidic solution is between 2 and 5; the organic solution is prepared by deionized water and a polymer.
[0014] Furthermore, the molar ratio of the molybdenum source, the niobium source and the tungsten source is 0.5:14:2.5 to 2.5:14:0.5; 1 to 3 g of organic acid is added to 20 ml of deionized water; and 0.5 to 2 g of polymer is added to 20 ml of deionized water.
[0015] Furthermore, the molybdenum source is one of ammonium molybdate, molybdenum acetylacetonate, and molybdenum pentachloride; the niobium source is one of niobium oxalate, ammonium niobate, or niobium pentachloride; and the tungsten source is ammonium metatungstate or tungsten hexachloride.
[0016] Furthermore, the organic acid is one of oxalic acid, acetic acid, ascorbic acid, citric acid, and malic acid; and the polymer is one of polyvinyl pyrrolidone, polyvinyl alcohol, or polyacrylonitrile.
[0017] In a second aspect, the present invention provides a molybdenum niobium tungsten oxygen fast-charging negative electrode material prepared by the above method.
[0018] In a third aspect, the present invention provides the use of the above-mentioned molybdenum niobium tungsten oxygen fast-charging negative electrode material in the preparation of lithium battery negative electrode materials.
[0019] The beneficial effects of the present invention are:
[0020] 1) Mo 5+ The doping of Nb(W)O6 weakens the octahedral symmetry and increases the distortion of Nb(W)O6 in NbWO, which is beneficial to reduce the Li + Diffusion barrier (this is Li + rate-limiting step of diffusion).
[0021] 2) The present invention provides a micron-sized secondary particle composed of nanoparticles, which utilizes a low-crystallinity crystal structure to improve the electrical conductivity and ion diffusion rate, and has a capacity retention rate of 87% after 2000 cycles at a high rate of 50C, while avoiding the problem of low compaction density of nanoparticles.
[0022] 3) The present invention utilizes a gel calcination method for doping, which is simple, has low energy consumption (compared to other niobium oxides), loose preparation conditions, and can be completed by heating under natural conditions such as air, avoiding harsh conditions such as inert atmosphere, high voltage, high current, and violent combustion, and has practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is the XRD pattern of the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material prepared in Example 1 of the present invention;
[0025] Figure 2 This is a Raman graph of the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material prepared in Example 1 of the present invention;
[0026] Figure 3 This is a SEM image of the molybdenum, niobium, tungsten and oxygen fast-charging negative electrode material prepared in Example 1 of the present invention;
[0027] Figure 4 This is a long cycle test diagram of the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material prepared in Example 1 of the present invention;
[0028] Figure 5 This is a rate performance diagram of the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The principles and features of the present invention are described below in conjunction with the accompanying drawings and specific embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0030] Niobium-based oxides are candidates for embedded negative electrode materials for lithium-ion batteries due to their high rate capability, high capacity and safe operating voltage. These materials all show good fast charging performance due to the Wadsley-Roth crystal shear structure, but there is a significant capacity decay during long cycles at higher rates (20C). The inventors have effectively improved the electrochemical performance by introducing two metal elements, molybdenum and tungsten. The technical solution is as follows:
[0031] The present invention provides a method for preparing a molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material. A molybdenum source, a niobium source and a tungsten source are dissolved in an acidic solution, and a certain amount of an organic solution is prepared at the same time. The two solutions are fused to form a gel, and an organic-inorganic mixed solid is obtained after dehydration treatment. The molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material is prepared by a high-temperature calcination method.
[0032] Preferably, the specific steps of the high-temperature calcination method are: drying the gel under high-temperature vacuum conditions to obtain an organic-inorganic mixed solid, pre-calcining it at a low temperature to obtain a precursor, pressing the precursor into a round cake shape and then calcining it at a high temperature to obtain a molybdenum niobium tungsten oxygen fast-charging negative electrode material.
[0033] Preferably, during the high temperature vacuum process, the temperature is in the range of 80 to 160° C., the vacuum degree is in the range of 0.8 to 1.0 MPa, and the time is in the range of 10 to 15 hours; the mixed solid is kept at 300 to 450° C. for 6 to 8 hours to obtain a precursor.
[0034] Preferably, the precursor is pressed into a cake shape at a pressure of 500 to 1000 MPa; and the molybdenum niobium tungsten oxygen fast-charging negative electrode material is obtained by keeping the temperature at 700 to 1000° C. for 5 to 10 hours.
[0035] Preferably, the acidic solution is prepared by deionized water and an organic acid, and the pH value of the acidic solution is between 2 and 5; the organic solution is prepared by deionized water and a polymer.
[0036] Preferably, the molar ratio of the molybdenum source, the niobium source and the tungsten source is 0.5:14:2.5 to 2.5:14:0.5; 1 to 3 g of organic acid is added to 20 ml of deionized water; and 0.5 to 2 g of polymer is added to 20 ml of deionized water.
[0037] In some preferred embodiments, the molybdenum source is one of ammonium molybdate, molybdenum acetylacetonate, and molybdenum pentachloride, the niobium source is one of niobium oxalate, ammonium niobate, or niobium pentachloride, and the tungsten source is ammonium metatungstate or tungsten hexachloride.
[0038] In some preferred embodiments, the organic acid is one of oxalic acid, acetic acid, ascorbic acid, citric acid, and malic acid; and the polymer is one of polyvinyl pyrrolidone, polyvinyl alcohol, or polyacrylonitrile.
[0039] The following are specific embodiments.
[0040] Example 1
[0041] 1. Dissolve 10g oxalic acid in 150ml deionized water to prepare an acidic solution, and then dissolve 15g niobium oxalate, 0.6g ammonium molybdate and 1g ammonium metatungstate in the above solution;
[0042] 2. Dissolve 5 g of polyvinyl pyrrolidone in 50 ml of deionized water; then mix the acidic solution obtained in the first step with the water to obtain a gel solution;
[0043] 3. The gel solution was placed in an oven at a vacuum degree of 1.0 MPa and a temperature of 120°C and dried for 12 hours to obtain a solid mixture;
[0044] 4. Transfer the solid mixture to a muffle furnace at 350°C and pre-calcine for 6 hours to obtain a precursor;
[0045] 5. Use a press and a tableting mold to press the precursor into a round cake at a pressure of 500 MPa, and then transfer it to a 700°C muffle furnace and calcine it for 10 hours to obtain a molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material.
[0046] The molybdenum-niobium-tungsten-oxygen fast-charge negative electrode material prepared in Example 1 was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman spectrometer (Raman), etc., and the following was obtained: Figure 1-3 The result graph is shown.
[0047] Figure 1 This is the XRD diagram of the molybdenum, niobium, tungsten and oxygen fast-charging negative electrode material. Figure 1 It can be seen that the Bragg diffraction peaks of the three materials, molybdenum niobium tungsten oxide (MNWO), niobium tungsten oxide with a small amount of tungsten missing (NW2) and traditional niobium tungsten oxide (NW3), are all located at similar peak positions and coincide with the characteristic diffraction peaks of niobium tungsten oxide, proving that the introduction of molybdenum atoms and the small amount of tungsten atoms missing did not destroy the overall structure of the material. At the same time, there are no other impurity peaks, proving the good crystallinity and pure phase characteristics of the material. In contrast, the peak intensity of MNWO is significantly reduced and the half-peak width is significantly increased, proving that molybdenum atoms reduce the crystallinity of niobium oxide.
[0048] Figure 2 This is the Raman spectrum of the molybdenum, niobium, tungsten and oxygen fast-charging negative electrode material. Figure 2It can be seen that the peak positions of the three samples are similar, indicating that they can be attributed to the same bulk structure; Region 1 and Region 2 correspond to MO bonds and MOM bonds (M represents metal), respectively, Region 3 corresponds to the MO vibration of the NbO6 octahedron, and Region 4 represents the MO vibration of the WO6 octahedron; Overall, compared with NW3 and NW2, MNWO has lower peak intensity and lower peak width, and this phenomenon is more prominent in Region 3, specifically, the MO vibration peak of the NbO6 octahedron of NW3 is the strongest, the corresponding peak of NW2 almost disappears, and the corresponding peak of MNWO is weaker. Because the MO vibration peak of the WO6 octahedron has basically not changed, it proves that the molybdenum atom mainly affects the electronic properties of the Nb atom; and because XRD proves that MNWO has low crystallinity, it can be inferred that the molybdenum atom causes lattice distortion or reduced octahedral symmetry inside the material.
[0049] Figure 3 This is the SEM image of the molybdenum-niobium-tungsten-oxygen fast-charge negative electrode material. Figure 3 It can be seen that MNWO is a micron-sized secondary particle composed of nano-sized regular particles, and the micron-sized size exceeds 10 microns. Combined with its low crystallinity, it can be judged that the formation of large particles is not generated by a single grain, and crystal distortion or disordered areas may appear inside the crystal structure, and molybdenum atoms play a key role.
[0050] The molybdenum niobium tungsten oxide fast-charging material prepared in Example 1 can be applied to the negative electrode of a lithium-ion battery. The lithium battery includes a negative electrode sheet, a positive electrode sheet, a diaphragm, and an electrolyte that impregnates the diaphragm. The preparation method of the negative electrode sheet includes: using the molybdenum niobium tungsten oxide material as an active material, Ketjen black as a conductive agent, and polyvinylidene fluoride as a binder, mixing and evenly coating them on a carbon-coated aluminum foil, and forming the negative electrode sheet after drying. The mass ratio of the molybdenum niobium tungsten oxide negative electrode material, the Ketjen black, and the polyvinylidene fluoride is 7 to 8:1 to 2:1.
[0051] The molybdenum-niobium-tungsten-oxygen fast-charge negative electrode material prepared in Example 1 was subjected to electrochemical performance testing by constant current charge and discharge. Figure 4-5 The result graph is shown.
[0052] Figure 4 This is a long cycle test diagram of molybdenum, niobium, tungsten and oxygen fast charging negative electrode materials. Figure 4 It can be seen that MNWO has a current density of 160 mAh g at 20 C. -1 The specific capacity is 130 mAh g at a current density of 50 C. -1 The specific capacity is much higher than that of NW3 (120 mAh g -1 and 109mAh g -1After 2000 cycles, MNWO showed a capacity retention rate of 86% (20C) and 87% (50C), which is also higher than the 81% capacity retention rate of NW3. At a current density of 50C, the capacity of NW3 was only 74% after 1600 cycles, proving that molybdenum niobium oxide has higher capacity and longer cycle life, and the fast charging performance has been greatly improved.
[0053] Figure 5 This is the rate performance diagram of molybdenum, niobium, tungsten and oxygen fast charging negative electrode materials. Figure 5 It can be seen that MNWO exhibits 200mAh g at 5C condition. -1 The specific capacity is 106 mAh g at a high rate of 100C. -1 , which fully proves the excellence of its fast charging performance.
[0054] Example 2
[0055] 1. Dissolve 10g of acetic acid in 150ml of deionized water to prepare an acidic solution, and then dissolve 15g of niobium pentachloride, 2.9g of molybdenum pentachloride and 2g of ammonium metatungstate in the above solution;
[0056] 2. Dissolve 5 g of polyvinyl pyrrolidone in 50 ml of deionized water; then mix the acidic solution obtained in the first step with the water to obtain a gel solution;
[0057] 3. The gel solution was placed in an oven at a vacuum degree of 1.0 MPa and a temperature of 120°C and dried for 12 hours to obtain a solid mixture;
[0058] 4. Transfer the solid mixture to a muffle furnace at 350°C and pre-calcine for 6 hours to obtain a precursor;
[0059] 5. Use a press and a tableting mold to press the precursor into a round cake at a pressure of 500 MPa, and then transfer it to a muffle furnace at 800°C and calcine for 8 hours to obtain a molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material.
[0060] Example 3
[0061] 1. Dissolve 10g of citric acid in 150ml of deionized water to prepare an acidic solution, and then dissolve 15g of ammonium niobate, 2.1g of ammonium molybdate and 2.1g of tungsten hexachloride in the above solution;
[0062] 2. Dissolve 5 g of polyvinyl alcohol in 50 ml of deionized water; then mix the acidic solution obtained in the first step with the water to obtain a gel solution;
[0063] 3. The gel solution was placed in an oven at a vacuum degree of 1.0 MPa and a temperature of 120°C and dried for 12 hours to obtain a solid mixture;
[0064] 4. Transfer the solid mixture to a muffle furnace at 350°C and pre-calcine for 6 hours to obtain a precursor;
[0065] 5. Use a press and a tableting mold to press the precursor into a round cake at a pressure of 500 MPa, and then transfer it to a 700°C muffle furnace and calcine it for 10 hours to obtain a molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material.
[0066] Through performance characterization, both Example 2 and Example 3 prepared niobium tungsten oxides with ordered alternating symbiotic crystal structures.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material, characterized in that a molybdenum source, a niobium source and a tungsten source are dissolved in an acidic solution, and a certain amount of an organic solution is prepared at the same time, the two solutions are fused to form a gel, and an organic-inorganic mixed solid is obtained after dehydration treatment, and the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material is prepared by a high-temperature calcination method.
2. The method for preparing the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material according to claim 1, characterized in that: The specific steps of the high-temperature calcination method are: drying the gel under high-temperature vacuum conditions to obtain an organic-inorganic mixed solid, pre-calcining it at a low temperature to obtain a precursor, pressing the precursor into a round cake shape and then calcining it at a high temperature to obtain a molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material.
3. The method for preparing the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material according to claim 2, characterized in that: During the high-temperature vacuum process, the temperature is within the range of 80 to 160° C., the vacuum degree is within the range of 0.8 to 1.0 MPa, and the time is within 10 to 15 hours; the mixed solid is kept at 300 to 450° C. for 6 to 8 hours to obtain a precursor.
4. The method for preparing the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material according to claim 2, characterized in that: The precursor is pressed into a cake shape by a pressure of 500 to 1000 MPa; and then kept at 700 to 1000° C. for 5 to 10 hours to obtain the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material.
5. The method for preparing the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material according to any one of claims 1-2, characterized in that: The acidic solution is prepared by deionized water and an organic acid, and the pH value of the acidic solution is between 2 and 5; the organic solution is prepared by deionized water and a polymer.
6. The method for preparing the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material according to any one of claims 1 to 5, characterized in that: The molar ratio of the molybdenum source, the niobium source and the tungsten source is 0.5:14:2.5 to 2.5:14:0.5; 1 to 3 g of organic acid is added to 20 ml of deionized water; and 0.5 to 2 g of polymer is added to 20 ml of deionized water.
7. The method for preparing the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material according to any one of claims 1 to 6, characterized in that: The molybdenum source is one of ammonium molybdate, molybdenum acetylacetonate and molybdenum pentachloride; the niobium source is one of niobium oxalate, ammonium niobate and niobium pentachloride; and the tungsten source is ammonium metatungstate or tungsten hexachloride.
8. The method for preparing the molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material according to any one of claims 1 to 7, characterized in that: The organic acid is one of oxalic acid, acetic acid, ascorbic acid, citric acid and malic acid; the polymer is one of polyvinyl pyrrolidone, polyvinyl alcohol or polyacrylonitrile.
9. A molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. The molybdenum-niobium-tungsten-oxygen fast-charging negative electrode material according to claim 9 is used in the negative electrode of a lithium battery.
Citation Information
Cited By
Preparation method and low-temperature application of Te-doped tungsten niobium oxide / molybdenum niobium oxide heterojunction material
CN121990610A